Inovasi E-Book Berbasis Blended Learning Menggunakan Aplikasi Sigil pada Mata Kuliah Biokimia: (E-Book Innovation Based on Blended Learning Using Sigil Application in Biochemistry Courses) - Miftahussa’adiah, Miftahussa’adiah; Ladisa, Stevia; Romadhan, Muhammad Fauzi (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2025)
This research to produce a valid and practical e-book teaching content product. The method used in this study is Research and Development (RnD) with the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The data in this study were obtained through expert validation questionnaires (content experts, media experts, and language experts) and student response questionnaires on blended learning-based biochemistry e-book products using the developed sigil application. Data analysis techniques were carried out by referring to the standard criteria for validity and practicality of e-books. The results of the study were obtained based on the results of the media expert validity questionnaire (98%), content experts (98%), language experts (91%) with a very valid category, and field practitioners consisting of questionnaires filled out by lecturers who teach biochemistry courses (91.66%) and students as a form of readability from e-book users (97.86%). Therefore, it can be concluded that blended learning-based e-books using the sigil application in biochemistry courses are valid and practical for use in learning activities. Key words: e-book, Biochemistry, Blended Learning, Sigil application